(untitled) (Biological Sciences - PJSIR, 2007)
Seeds of Si/ybum marianum (mi l k th istle) plant were collected from Peshawar valley and eval uated. Study revealed 26.65% ± 0.25 fixed oi l and 23.0% ± 0.38 protein. The oil extracted has l i nolei c acid (64.59%), oleic acid (23.59%), pal mitic acid (12.62%), and stearic acid (5.9%) as major fatty acids. Proxi mate pri nci pals, mi nerals and oil quality indices were determi ned. The carbohyd rate content is q ui te h igh (37.72 ± 1 .64%), whi l e i t h as low crude fi bre contents (4.55 ± 0.23%). The seed oi l shows the followi ng physicochemical characteristics: 1 3.67 ± 0.23 meq/kg of peroxide val ue; 1 94.78 ± 0.23 of saponificati on val ue; I 03. 89 ± 0.56 g/100 g of iodi ne val u e and acid va l ue of 1.93 ± 0.34%. The un sapon i fi abl e matter (UNS) of the oi l was 2 .36% ± 0.45. The resul ts of n utri tional l y val uable mi nerals i ndi cates that seeds contai n s Mg 2,225 ppm , Ca 778.5 ppm, Cu 1 08.3 ppm, Fe 74.3ppm, Zn 69.4 ppm, Pb 44.3 ppm , N i 35.5 ppm, Mn 23.5 ppm, Cr 6.8 ppm and Cd 3.2 ppm was found i n lowest concentration. Th e q ual i tative anal ysis by th i n layer chromatographic (TLC) technique for the protei n hydrolyzate revealed ten amino acids. Among these aspart i c acid, glyci ne, gl utamic acid and cystei ne were the major amin o acid s. Resu l ts of this prel i mi nary i nvest igation i nd icated t h at t h e oi l might be edible as i nferred from its chemical composition and fatty acid profile